A Rare Case Of Advanced Vulval Cancer In A Perimenopausal Nulliparous Woman (Journal of Pharmaceutical Negative Results, 2023)
3-5% of female genital tract malignancies are vulval cancers, with squamous cell carcinoma being the most prevalent histological type (95%), followed by melanoma, sarcoma, and basalioma. Based on the aetiology, it is classified into two types: the first type is attributed with human papillomavirus (HPV) infection, while the second is without HPV. Vulval pruritis is most frequent complaint seen. The mortality rate for vulvar cancer decreased, and quality of life increased as a result of modern treatment choices.There are many gynaecologists who have rarely seen the case of Vulval cancer. We here present a case of vulval cancer in 45-year-old patient who was symptomatic and incidentally diagnosed which was managed successfully with surgery followed by post-operative chemotherapy for 3 cycles.